(untitled) (SS Multidisciplinary Research Journal, 2025)
This is an ethnographic study of the local community’s relation with Adinath temple located in Chobhar, Kirtipur, and their perception and meaning making of such relation with the Adinath. This study examines how both the Hindu and Buddhist devotees visiting the Adinath temple relate their own religious and cultural identities and associations with the temple. It follows explorative and interpretive approach to gain the insider perspectives of the local residents and their meaning making in relation to their association with the Adinath. Further, it has explored the issue of Hindu-Buddhist polytropic existence based on the concept discussed by David Gellner (2005). Employing ethnographic methodology, it has examined how the local people made sense of both the Hindu-Buddhist cultural contours of the temple, the associated legends and stories, and the complex cosmology of their everyday experience with Adinath, living in a multi-cultural and multi-religious society.